OVERUSE OF ANTIBIOTICS IN DENTISTRY. A CRITICAL REVIEW - Faisal Alshail*, Turki Almohaid, (Chelonian Research Foundation, 2024)
Antimicrobial resistance (AMR) has been on the rise worldwide because of excessive and inappropriate use of antibiotics in healthcare. Dentists account for 10% of all antibiotic prescriptions, primarily used to treat oral infections and prevent postsurgical problems. Recent research and clinical assessments emphasize new therapy strategies that involve decreasing antibiotic dosages and prescriptions. Prioritizing precise diagnosis and enhancing oral health before dental procedures and in patients' everyday routines is essential. This article identifies and summarizes the most frequent clinical and operative scenarios in dental practice, including endodontics, acute alveolar abscess management, extractive oral surgery, periodontology, and implantology. It suggests potential guidelines to decrease antibiotic prescription and usage while maintaining high success rates and low complication rates. The patient categories that need antibiotics for existing conditions are also summarized. Establishing particular standards for antibiotic therapy is crucial in reducing the potential of antimicrobial resistance. Recent evaluations show that in dentistry, lowering antibiotic use by carefully evaluating patient conditions and interventions might enhance efficacy, decrease unwanted effects, and promote individualized treatment. Keywords: Antibiotics, Oral infections, Antimicrobial resistance, Dental medicine.